Indian Agriculture needs a Strategic Shift for Improving Fertilizer Response and Overcome Sluggish Foodgrain Production - Gupta, Raj; Benbi, DK; Abrol, IP (Journal of Agronomy Research, 2021)
In India, loss of fertility through soil erosion is primarily a summer monsoons mediated phenomenon. Reversing the land degradation processes contribute to water availability, soil fertility maintenance, adapting to climate change and overall food security. Whereas kharif (monsoon/rainy season crop) foodgrain production largely depends on summer monsoons, the rabi season (post-rainy season/winter crop) rainfall is too little to exert a direct influence. In spite of larger acreage under kharif foodgrain crops, total fertiliser consumption during kharif and rabi seasons is comparable. Negative rainfall anomalies (deficit) adversely affected total fertiliser consumption and their use efficiency. Despite significant differences in fertiliser application rates, the response to applied fertiliser nutrients is almost similar in the two seasons. This implies that nutrient use efficiency (NUE) has a ‘manageable’ and an ‘unmanageable’ component wherein 4R practices are difficult to implement under unfavourable kharif weather conditions. Partial factor productivity of fertilizer nutrients (PFPF) has continuously declined over decades mainly because of depletion of soil organic carbon, imbalanced use of nutrients and inability to maintain soil moisture supplies. These observations plus yield-gap analysis permitted us to conclude that past trends of declining NUE can only be reversed through a shift either in sustainable land management practices or enhancing the genetic yield potential/ biomass of crop cultivars or by combining both and making kharif crop planting independent of monsoons rains through direct dry seeding.
Keywords: Conservation agriculture; kharif and rabi seasons; nutrient use efficiency; partial factor productivity; rainfall anomaly; soil organic carbon; yield gap.